(untitled) (The Harvest, 2026)
This article reexamines William Shakespeare’s The Tempest using Karen J. Warren’s ecofeminist perspective, offering a critical examination that explores the connections between gender and environmental oppression. Utilizing close reading and thematic analysis, the research examines the power relationships among characters; binary thinking that upholds hierarchical frameworks, and depictions of human-nature connections. The paper focuses on the female subjugation as reflected in the relationship among creatures in both human and animal kingdoms. The results show that The Tempest critiques patriarchal dominance and environmental degradation, providing an understanding of how the play mirrors systemic patterns of oppression. This examination highlights the significance of Warren’s ecofeminist framework in revealing complex layers in Shakespeare’s writings, affecting education, activism, and policy, while underscoring the importance of literary studies in modern debates on environmental justice and gender equity.